Estudo dos processos de geração e transferência de cargas em corantes cianinas - Vismara, Marcus Vinícius Gonçalves [UNESP] (2015)
The eyanines dyes have good potential as an active layer of organic solar cells, for example, they are strong absorbers of visible and infrared light, can be manufactured using very simple techniques, with low cost and good mechanical flexibility. However, they present problems such as low eletronic conductivity and solar cells based on these materials exhbit low efficiencies. In this context, this study aimed to understand the photoinduced charge generation and transfer processes is blends of dyes based on cyanine acting as electron acceptors or donors for use in organic solar cells. Trimethine dyes (Cy3) and heptamethine dye (Cy7) with different counterions were used. The main technique used in this study were the Electronic Spin Resonance (ESR) and its variation with the application of light during the measurement (LESR) at temperature of 77 K. We studied the effect of different dyes, as well as the effect of its counterions in the charge generation and transfer. For the analysis of results were simulated the ESR and LESR spectra for each paramagnetic species observed through software EasySpin. Acting as electron acceptor in blends with the MEH-PPV polymer, the dyes blends with Cy3 dyes showed better photo-induced charge generation and transfer compared Cy7 dyes. However, working as electron donors in blends with C60 fullerene the opposite effect was observed, where the blends with Cy7 dyes show a better photo-induced charge generation and transfer than blends with Cy3 dyes. Moreover, the ESR and LESR results showed different signals for (C60)1- changing only the conunterions of the dye, which can be explained based on morphological studies. Finally, the samples oxidation studies were conducted to verify the originals of LESR signals at lower magnetic fields